TECTONIC DEFORMATION OF GRANITES IN THE TIEN SHAN AND TRANSBAIKAL REGIONS - Leonov M.G.; Morozov Y.A.; Nikitin A.V. (My University, 2007)
Study of manifestation modes of the 3D mobility of crystalline rocks of the basement is a crucial issue in geology. Interest in this issue arose as early as the 1960s. However, investigations in this field virtually ceased in the 1970s–1980s. They were revived in the early 1990s in connection with the publication of new facts and theoretical approaches, as well as new achievements in mesomechanics and mechanics of granular media. Basement rocks, granites included, are undoubtedly subjected to significant structural transformations. Granites make up cold crystalline protrusions after evolution as magmatic bodies. These positive morphological structures are characterized by specific structural properties, which suggest that their exhumation can be attributed to 3D mobility and rheid (from Greek ρεο meaning “to flow”) deformation and such structures can be considered as crystalline protrusions. Descriptions of granite protrusions are rare in the literature, and manifestation modes of 3D deformations are insufficiently studied, although elucidation of the 3D mobility of rocks has principal significance for understanding tectonics of the consolidated crust, for example, for elucidating mechanisms of the exhumation of abyssal masses. The problem is also of practical importance, since the tectonic structure of granite massifs determines their oil and gas potential. We studied 3D deformations in some granite massifs of the Transbaikal and Tien Shan regions.